Self-supporting web design and crash analysis of eco-hybrid composite for fuselage subfloor application - Logadhasan Suwedan, author; Haris Ahmad Israr Ahmad, supervisor 447070; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2017